Profile of Non-Viral Risk Factors in Nasopharyngeal Carcinoma at RSUP Dr. M. Djamil Padang - Khansa Nihlatiyah Izzati; Sukri Rahman; Fathiya Juwita Hanum (Fakultas Kedokteran Universitas Andalas, 2026)
Profile of Non-Viral Risk Factors in Nasopharyngeal Carcinoma at RSUP Dr. M. Djamil Padang Background: Nasopharyngeal carcinoma is a malignancy originating from the nasopharyngeal epithelium and is one of the rarest cases of malignancy in the world. There are several non-viral factors that influence nasopharyngeal carcinoma. The purpose of this study was to determine the frequency distribution of non-viral risk factors for nasopharyngeal carcinoma, namely age, gender, occupation, family history, smoking, alcohol consumption, consumption of salted fish, and exposure to wood smoke and wood dust. Methods: This study is a descriptive study with a case-control design, with nasopharyngeal carcinoma patients as cases and patients with diagnoses other than nasopharyngeal carcinoma as controls. The sample size for this study was 20 for each case and control sample, analyzed using cross-tabulation tests. Results: The nasopharyngeal carcinoma patient showed that the majority of patients were aged between 46 and 55 years old and were predominantly male. The most common occupation was in the service and sales sector. Most patients had no family history of nasopharyngeal carcinoma. The majority of patients were non smokers, had never consumed alcohol, and rarely consumed salted fish. The most common patients were those who had never been exposed to wood smoke and wood dust. Conclusion: Non-viral risk factors associated with nasopharyngeal carcinoma were age 46–55 years, male sex, and employment in trade and sales services.